Evaluation of efficiency of artificial intelligence-based orthodontic treatment planning: A cross-sectional questionnaire study - Abdulrahman Mohammed Algethami; Raghu Devanna Pamayya; Yousef Mohammed Althomali; Abdulrahman Hassan Alzahrani; Mohammed Khalil Fahmi; Amith Vasanthakumar Holenarasipur; Ahmad Hatem Kariri; Muwffak Ghazi Alghoraibi; Matar Abdulrahman Alzahrani; Muaath Hussain Alzahrani (Saudi Journal of Oral Sciences)
Introduction: Artificial intelligence (AI) in orthodontics has shown a promise in improving diagnosis and treatment planning processes. This study examines how well AI works for orthodontic treatment planning and how dentists perceive it. An international validated questionnaire survey was distributed to dental professionals. Aim: The aim of the study was to evaluate the efficiency of AI in orthodontic treatment planning and its acceptance by dental practitioners. Materials and Methods: a cross-sectional survey was done on orthodontic practitioners, residents, and interested undergraduate students from the Orthodontic Division, Department of Preventive Dentistry, Faculty of Dentistry, Taif University, Taif, Saudi Arabia. A questionnaire was used to collect data bout the participants’ use of AI in orthodontic diagnosis and treatment planning. Results and Discussion: The survey showed that 92% of dental professionals were generally aware of AI and its use in orthodontics. In addition to noting AI’s potential for precise data, 84% of the participants stressed the value of human expertise in thorough orthodontic analyses. Furthermore, most of the respondents (80%) thought that AI could not completely replace orthodontists. Conclusion: AI is a useful diagnostic tool that improves dental professionals’ knowledge in the planning of orthodontic treatments. It is not, however, a replacement for the expertise of experienced specialists in providing precise diagnoses and treatment plans. More research is needed to maximize AI applications and ensure their smooth integration into orthodontic practices.